The Impact of Genocide in Gaza on Regional Security: Jordan’s Relevance in Supporting Palestine - Muhamad Fajar Pramono; Dwi Ardiyanti; Ida Susilawati; Sofi Mubarok (Indonesian Red Crescent Humanitarian Journal, 2026)
This study aims to analyze the geopolitical impact of the Hashemite Kingdom of Jordan on its support for Palestine in the context of the Israeli-Palestinian conflict. Using a geopolitical theoretical framework, this study explores Jordan's dynamic relationship with Palestine before and after the 1994 normalization of Jordanian-Israeli relations. The study also highlights Jordan's strategic role in maintaining regional stability and its response to geopolitical changes in the Middle East. This research uses a qualitative approach based on literature analysis to examine the political, economic and strategic dynamics that influence Jordan's stance towards Palestine. Based on the analysis, it is found that key geopolitical factors such as Jordan's strategic location, limited resources, and historical role as custodian of Jerusalem's holy sites influence its foreign policy. Jordan uses a pragmatic approach to deal with geopolitical pressures, including technological cooperation and water desalination with Israel. The main findings show that although Jordan normalized relations with Israel for the sake of stability and economic benefits, the country continues to support Palestine diplomatically, especially on issues such as Jerusalem and Palestinian rights. However, domestic challenges and external pressures often make this policy complex and sometimes contradictory. This research concludes that Jordan's geopolitics influenced it support to Palestine.